Analysis of Student Performance Differences in Computer Network Courses with Learning Modes in Multimedia Nusantara University - Junike, Livia; Yapranata, Karen; Halim, Fransiscus Ati (Universitas Multimedia Nusantara, 2025)
Global academic environments have been significantly impacted by the change in educational delivery techniques brought about by the COVID-19 pandemic. This study examines the variations in student performance in Multimedia Nusantara University's Computer Network course across on-site, hybrid, and online learning modes. 526 students data (2019–2022) were evaluated using a variety of statistical techniques, such as the Kruskal-Wallis test, tests for homoscedasticity and normality, pairwise comparison, and post-hoc Dunn's analysis. By taking into consideration the various circumstances and difficulties presented by each learning mode, these techniques guaranteed a thorough assessment of performance variances.